The Value-Added Analysis and Affecting Factors Coconut Sugar Offers (Case Study: Coconut Sugar Maker in Manyampa Village Ujung Loe District Bulukumba Regency) - Amrina Amrina; Ine Fausayana; Muhammad Aswar Limi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study aimed to determine the value of processing coconut sap into coconut sugar. In Manyampa Village, Ujung Loe Subdistrict, and the factors that affect the supply of coconut sugar in Manyampa Village, Ujung Loe Subdistrict, carried out from August to December 2021. Location determination was determined intentionally. Determination of the number of samples using the saturated sampling method because the number of pieces is relatively small, amounting to 15 respondents. Variables in this research consist of respondent identity and value-added analysis of coconut sugar derived from coconut sap. This data was analyzed using value-added analysis and Multiple Linear Regression Analysis. The results showed that the added value generated from one month of making coconut sugar in the village of Manyampa, Ujung Loe sub-district, was high, with an added value ratio of >50, with a percentage of 85%. And simultaneously, the supply of coconut sugar in Manyampa Village, Ujung Loe District, is influenced by the price of raw materials and other goods. The number of producers, Partially only raw material variables, affects the supply of coconut sugar. In contrast, the price of coconut sugar, the number of producers, and the costs of other goods do not affect the supply of coconut sugar.